Efficacy of acupuncture for pain relief in patients receiving extracorporeal shock wave lithotripsy: a meta-analysis of randomized controlled studies - Chen, Hsiao-Tien; Hung, Kuo-Chuan; Hsu, Yao-Chin; Kuo, Jinn-Rung; Chang, Ying-Jen; Chen, I-Wen; Sun, Cheuk-Kwan (Frontiers in Medicine, 2023)
Background: This meta-analysis aimed at investigating the efﬁcacy of acupuncture for pain relief in patients receiving extracorporeal shock wave lithotripsy (ESWL). Methods: Randomized controlled trials comparing the efficacy of acupuncture with conventional treatments were retrieved from major electronic databases (e.g., MEDLINE, EMBASE, Cochrane Library) until August 28, 2022. The primary outcome was the response rate (i.e., rate of pain relief), while secondary outcomes included stone-free rate, satisfaction rate, duration of ESWL, peri-/post-procedural pain score, and risk of adverse events. Results: Thirteen eligible studies involving 1220 participants published between 1993 and 2022 were analyzed. Pooled results indicated that acupuncture had a better response rate compared to conventional treatments (RR=1.17, 95% CI: 1.06 to 1.3, p=0.003, seven trials, n=832). Despite no difference in ESWL duration (MD=0.02 minutes, 95% CI: -1.53 to 1.57, p=0.98, three trials, n=141), stone-free rate (RR=1.11, 95% CI: 1 to 1.25, p=0.06, six trials, n=498), and satisfaction rate (RR=1.51, 95% CI: 0.92 to 2.47, p=0.1, three trials, n=334) between the two groups, the acupuncture group had a lower risk of adverse events (RR=0.51, 95% CI: 0.33 to 0.79, p=0.003, five trials, n=327), peri- (MD=-1.91 points, 94% CI: -3.53 to -0.28, p=0.02, four trials, n=258 patient) and post-procedural (MD=-1.07, 95% CI: -1.77 to -0.36, p=0.003, four trials, n=335) pain score. Conclusion: The results of this meta-analysis showed that the use of acupuncture in patients receiving ESWL was associated with a higher pain relief rate and a lower risk of adverse events, suggesting feasibility of its use in this clinical setting.